Enhanced performance of Bacillus megaterium OSR-3 in combination with putrescine ammeliorated hydrocarbon stress in Nicotiana tabacum. Issue 2 (28th January 2021) - Tariq, Muniba; Shah, Anis Ali; Yasin, Nasim Ahmad; Ahmad, Aqeel; Rizwan, Muhammad
Abstract: Hydrocarbon stress (HS) has been causing decreased plant growth and productivity. Putrescine (Put) and growth promoting microbes are vital for plant growth and development under hydrocarbon stress. Current research work was carried out to evaluate the potential of Bacillus megaterium OSR-3 alone and in combination with Put to alleviate HS in Nicotiana tabacum (L.). The crude petroleum contaminated soil significantly reduced growth attributes of N. tabacum . B. megaterium OSR-3 inoculated plants subjected to HS exhibited improved photosynthetic rate, gas exchange characteristics, poline contents and protein level. Furthermore, bacterial inoculation enhanced the antioxidative activity of superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) in tobacco plants subjected to HS. The HS alleviation in B. megaterium OSR-3 inoculated N. tabacum can be credited to the heightened activity of antioxidative enzymes, reduction in hydrogen peroxide (H2 O2 ) and abridged synthesis of malondialdehyde (MDA). The increased synthesis of indole acetic acid (IAA) in HS stressed N. tabacum plants treated with co-application of B. megaterium OSR-3 and Put attenuated toxicity and amplified growth of plants. Additionally, the co-application of B. megaterium OSR-3 and Put also upregulated the activity of antioxidative enzymes and induced augmented level of proline and IAA in plants under HS regimes. Current research provides novel insight into the potential and mechanism of B. megaterium OSR-3 and Put in mitigation of HS in N. tabacum plants.